2020
DOI: 10.1200/jco.19.03279
|View full text |Cite
|
Sign up to set email alerts
|

CD4/CD8 T-Cell Selection Affects Chimeric Antigen Receptor (CAR) T-Cell Potency and Toxicity: Updated Results From a Phase I Anti-CD22 CAR T-Cell Trial

Abstract: PURPOSE Patients with B-cell acute lymphoblastic leukemia who experience relapse after or are resistant to CD19-targeted immunotherapies have limited treatment options. Targeting CD22, an alternative B-cell antigen, represents an alternate strategy. We report outcomes on the largest patient cohort treated with CD22 chimeric antigen receptor (CAR) T cells. PATIENTS AND METHODS We conducted a single-center, phase I, 3 + 3 dose-escalation trial with a large expansion cohort that tested CD22-targeted CAR T cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
273
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(313 citation statements)
references
References 34 publications
7
273
1
4
Order By: Relevance
“…Our hCD22.7-derived membrane distal-targeting CAR has not been functionally compared side-by-side with other membrane proximal-targeting CD22-scFvs used already in clinical trials, 15 21 with which Fry et al published discrete complete remission (CR) rates of 57% with a median remission duration of 6 moths in patients with R/R B-ALL treated with m971-CD22-CAR T cells 15 and in a more recent study they reported CR of 70% with a median relapse-free survival of 6 months. 23 However, the hCD22.7-CAR performs efficiently in vitro and in vivo using clinically relevant patient samples of B-ALL with different aggressiveness. This coupled to the long-term persistence of hCD22.7-CAR T cells, the lack of antigenic loss in vivo in the few CAR-resistant B-ALL cells, its high affinity, and its immunogenicity similar to m971 and HA22 CD22-scFvs provides support for its clinical validation as either single or tandem CD22–CD19-CAR for both naive and anti-CD19-resistant patients with B-ALL.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Our hCD22.7-derived membrane distal-targeting CAR has not been functionally compared side-by-side with other membrane proximal-targeting CD22-scFvs used already in clinical trials, 15 21 with which Fry et al published discrete complete remission (CR) rates of 57% with a median remission duration of 6 moths in patients with R/R B-ALL treated with m971-CD22-CAR T cells 15 and in a more recent study they reported CR of 70% with a median relapse-free survival of 6 months. 23 However, the hCD22.7-CAR performs efficiently in vitro and in vivo using clinically relevant patient samples of B-ALL with different aggressiveness. This coupled to the long-term persistence of hCD22.7-CAR T cells, the lack of antigenic loss in vivo in the few CAR-resistant B-ALL cells, its high affinity, and its immunogenicity similar to m971 and HA22 CD22-scFvs provides support for its clinical validation as either single or tandem CD22–CD19-CAR for both naive and anti-CD19-resistant patients with B-ALL.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…CRS can manifest clinically on a spectrum of acuity ranging from constitutional symptoms of fever, fatigue, headache, and myalgia to severe end-organ toxicity, hemodynamic shock, respiratory failure, and death [67,68,70]. In rare cases, CAR T cell therapy has been linked to the induction of an rHLH/MAS-like syndrome, which may be a progression to the most severe end of the CRS spectrum [75,76]. Common features of CRS as well as HLH and MAS are shown in Table 1.…”
Section: Cytokine Release Syndrome (Crs)mentioning
confidence: 99%
“…A prolonged life-threatening systemic inflammatory response resembling hemophagocytic lymphohistiocytosis (HLH) or macrophage activation syndrome (MAS) (10) has been increasingly recognized as one part of the spectra of toxicities occurring after anti-CD19 CAR T cell infusion or CD19-directed blinatumomab, a bispecific T cell engager therapy (14). HLH-like manifestations have also been seen after anti-CD22 CAR T cell therapy (16). HLH and MAS are clinical syndromes of pathologic hyperinflammation and uncontrolled macrophage activation associated with triggers such as viral infections and rheumatologic diseases (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…HLH and MAS are clinical syndromes of pathologic hyperinflammation and uncontrolled macrophage activation associated with triggers such as viral infections and rheumatologic diseases (17,18). Similarly, patients with CAR T cell-associated HLH-like toxicities present with prolonged cytopenia, hemophagocytosis, hyperferritinemia, fever, coagulopathy, liver function abnormalities, splenomegaly, and other organ dysfunction (14,16).…”
Section: Introductionmentioning
confidence: 99%